Ancient Roman sports, A-Z : athletes, venues, events and terms - Matz, David (McFarland & Company, Inc., Publishers, 2019)
"Chariot races. Gladiatorial combat. Fishing. Hunting. Swimming. This reference book contains more than 100 entries covering sporting events and activities of the era, and the Romans who sponsored, competed in and attended them. Brief abstracts of the entries are included for quick reference, along with an expansive glossary and biographical notes"--